Rozwiązanie:
a)
[tex]b_{n}=2^{3n+1}\\b_{n+1}=2^{3(n+1)+1}=2^{3n+4}\\q=\frac{b_{n+1}}{b_{n}} =\frac{2^{3n+4}}{2^{3n+1}} =2^{3}=8=const[/tex]
Zatem ciąg [tex]b_{n}[/tex] jest geometryczny.
[tex]b_{n+1}-b_{n}=2^{3n+4}-2^{3n+1}=2^{3n+1}(8-1)=7*2^{3n+1}[/tex]
Ponieważ [tex]n \in \mathbb{N}_{+}[/tex], to [tex]7*2^{3n+1}>0[/tex], co oznacza, że ten ciąg jest rosnący.
b)
[tex]b_{n}=5*4^{n}\\b_{n+1}=5*4^{n+1}\\q=\frac{b_{n+1}}{b_{n}} =\frac{5*4^{n+1}}{5*4^{n}} =4=const[/tex]
Zatem ciąg [tex]b_{n}[/tex] jest geometryczny.
[tex]b_{n+1}-b_{n}=5*4^{n+1}-5*4^{n}=5*4^{n}(4-1)=15*4^{n}[/tex]
Ponieważ [tex]n \in \mathbb{N}_{+}[/tex], to [tex]15*4^{n}>0[/tex], co oznacza, że ten ciąg jest rosnący.